"A Disease That's in My Flesh Which I Must Needs Call Mine": Lear, Macbeth and the Fear of Futurity. Issue 6 (18th August 2019) - Harper, Elizabeth
ABSTRACT: This essay offers a meditation on the terror of singularity as it manifests in Shakespeare's King Lear (1606) and Macbeth (1611). Drawing upon psychoanalytic and queer theory, in particular Lee Edelman's No Future: Queer Theory and the Death Drive (2004), it emphasises the centrality of the child to ideas of futurity and argues that the source of the tragedy in Lear and Macbeth is bound up with ambivalence about the relationship between children and selfhood. The essay approaches the tragedies as resources for understanding the fear of handing power over to a future generation ( King Lear ) and the problem of contending with the bleakness of mortality when you face the future in the absence of heirs ( Macbeth ). Through the figure of the tormented father (or would-be father) king, the essay traces the dark power of the parent–child relation especially by attending to characters who do not recognise that power.